1997
DOI: 10.2307/1592457
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Findings in the 1992 Epornitic of Neurotropic Velogenic Newcastle Disease in Double-Crested Cormorants from the Upper Midwestern United States

Abstract: Neurotropic velogenic Newcastle disease (NVND) occurred in juvenile double-crested cormorants, Phalacrocorax auritus, simultaneously in nesting colonies in Minnesota, North Dakota, South Dakota, and Nebraska and in Lakes Michigan, Superior, Huron, and Ontario during the summer of 1992. Mortality as high as 80%-90% was estimated in some of the nesting colonies. Clinical signs observed in 4- to 6-wk-old cormorants included torticollis, tremors, ataxia, curled toes, and paresis or weakness of legs, wings or both,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…Necropsy findings have previously been reported in a subset of American cormorants from this epizootic (Banerjee et al, 1994;Meteyer et al, 1997) and no consistent significant gross lesions were found in the additional DCC reported here, from the USA or Canada. Newcastle disease virus was isolated from birds from 15 USA colony sites in Minnesota, Nebraska, North Dakota and South Dakota, Lake Superior, Lake Michigan, Lake Huron and Lake Ontario (Table 1).…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…Necropsy findings have previously been reported in a subset of American cormorants from this epizootic (Banerjee et al, 1994;Meteyer et al, 1997) and no consistent significant gross lesions were found in the additional DCC reported here, from the USA or Canada. Newcastle disease virus was isolated from birds from 15 USA colony sites in Minnesota, Nebraska, North Dakota and South Dakota, Lake Superior, Lake Michigan, Lake Huron and Lake Ontario (Table 1).…”
Section: Resultssupporting
confidence: 58%
“…For each DCC colony, we tabulated estimated mortality (number of dead juveniles/estimated juvenile population) and presence/absence of clinical signs compatible with ND, microscopic lesions characteristic of ND in DCC (Wobeser et al, 1993;Banerjee et al, 1994;Meteyer et al, 1997), seropositive birds, and virus positive birds (Tables 1, 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Newcastle disease caused high mortality in cormorant chicks in , 1992, and 1995(Wobeser et al, 1993Meteyer et al, 1997;Kuiken et al, 1998). However, without estimates of mortality rates from other causes, it was not possible to assess the relative importance of Newcastle disease to these cormorant populations.…”
Section: Introductionmentioning
confidence: 99%
“…Last-hatched chicks in broods of three or four commonly die of starvation due to non-aggressive sibling competition (Hunt and Evans, 1997). Mortality from Newcastle disease, which generally occurs after chicks have left their nests, was estimated at 10 to 90% of young of the year (Meteyer et al, 1997;Kuiken et al, 1998).…”
Section: Introductionmentioning
confidence: 99%